1987
DOI: 10.1111/j.1532-950x.1987.tb00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Y‐U Pyloroplasty on Gastric Emptying and Duodenogastric Reflux in the Dog

Abstract: A Y-U pyloroplasty was performed on five healthy adult dogs. Gastric emptying half times (t1/2 GE) of a canned food meal were measured by scintigraphy three times before surgery and three times from 6 to 8 weeks after surgery. Fluoroscopic studies of gastric and duodenal motility were made before surgery and 3, 7, and 35 days after surgery. Clinical observations were made daily throughout the study. Gross and histologic evaluations of the gastroesophageal and pyloric regions were performed at the termination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In our study, the total gastric emptying time varied between 5 and 11 h in the preoperative period. Other studies have reported a complete gastric emptying time of around 5–15 h in normal dogs and a great individual variability in these results 5,14–16 . The variability of gastric emptying times obtained in this study could be influenced by different factors, such as animal breed, age, sex, or size 14,16 …”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In our study, the total gastric emptying time varied between 5 and 11 h in the preoperative period. Other studies have reported a complete gastric emptying time of around 5–15 h in normal dogs and a great individual variability in these results 5,14–16 . The variability of gastric emptying times obtained in this study could be influenced by different factors, such as animal breed, age, sex, or size 14,16 …”
Section: Discussionmentioning
confidence: 50%
“…Nevertheless, the good results of pyloric surgery in dogs by conventional surgical approach have already been established by both research 14,17,19,20,23,42,43 and clinical studies. 1,4,5,13,32,33,44 In conclusion, we evaluated 20 dogs after conventional and laparoscopic pyloric surgery and concluded that a laparoscopic technique appears to be as effective as the open technique for accelerating gastric emptying. It can be postulated that laparoscopic surgery (e.g., laparoscopic Heineke-Mikulicz pyloroplasty) may offer an added advantage of decreasing gastric emptying time in dogs.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations